A8.21 Rapid downregulation of inflammatory cytokine production in cultured human macrophages after CTLA4-Ig, dexamethasone, and methotrexate combined treatments. (13th February 2015) - Cutolo, M; Montagna, P; Soldano, S; Sulli, A; Paolino, S; Pizzorni, C; Seriolo, B; Cimmino, M; Brizzolara, R
Abstract : Background and objectives: In rheumatoid arthritis (RA) the combination of the fusion protein CTLA4-Ig (abatacept) and other drugs such as glucocorticoids (GC) or/and methotrexate (MTX) allows to obtain better clinical improvement compared to CTLA4-Ig monotherapy. Our recent data showed that CTLA4-Ig, by interacting with the CD86 molecule on RA synovial macrophages, may induce reverse signalling with anti-inflammatory effects, involving NFkB intracellular pathway [1–4]. The anti-inflammatory effect of DEX alone or combined with CTLA4-Ig or/and with CTLA4-Ig plus methotrexate (MTX) was evaluated at gene expression level in cultured human activated macrophages. Materials and methods: THP-1 cells, activated into macrophages (PMA 0.05 g/ml; 24 h), were cultured for 3 and 24 h with DEX (10 −8 M) alone, DEX combined with CTLA4-Ig (500 g/ml) and DEX with CTLA4-Ig plus MTX (0.05 g/ml). Subsequently, qRT-PCR analysis for IL-1b, TNFa and IL-6 gene expression was performed. Cells untreated were used as controls. Results: After 3 h, qRT-PCR showed in macrophages treated with DEX alone or with DEX-CTLA4-Ig or DEX-CTLA4-Ig-MTX combined treatment, a significant reduction (p < 0.01) for the expression of all assayed cytokines, compared with controls. CTLA4-Ig alone after 3 hrs, also significant reduced IL-1b (p < 0.01), TNFa (p < 0.05) and IL-6 (p < 0.01) expression. After 24 h, DEX alone or DEX-CTLA4-Ig or DEX-CTLA4-Ig-MTX combined treatments still showed the most significant reduction (p < 0.01) only for IL-1b. After 24 h of DEX-CTLA4-Ig or DEX-CTLA4-Ig-MTX combined treatments TNFa and IL-6 gene expression were still decreased. On the contrary, TNFa and IL-6 gene expression after 24 h of DEX alone treatment resulted unchanged, compared to controls. CTLA4-Ig alone, after 24 h also induced a significant decrease in gene expression for TNFa (p < 0.05) and IL6 (ns), while IL1b expression was unchanged, compared to controls. Conclusions: DEX and DEX-CTLA4-Ig or DEX-CTLA4-Ig-MTX combined, induced a rapid anti-inflammatory effect on cultured human macrophages, by decreasing proinflammatory cytokine gene expression already after 3 h of treatment. These results seem well correlated with the clinical experience. References: Cutolo M, Soldano S, Montagna P, et al . Arthritis Res Ther 2009; 11 :176–85. Brizzolara R, Soldano S, Montagna P, et al . Reumatismo 2011; 63 :80–5. Brizzolara R, Montagna P, Soldano S, Cutolo M. J Rheumatol 2013; 40 (5):738–40. Cutolo M, Soldano S, Contini P, et al . Clin Exp Rheumatol 2013; 31 (6):943–6.